ANALYSIS OF THE DEVELOPMENT OF FINANCIAL MANAGEMENT CONCEPTS FROM THE PERSPECTIVE OF AGENCY THEORY AND CORPORATE VALUE: A LITERATURE REVIEW OF GLOBAL RESEARCH TRENDS AND STRATEGIC IMPLICATIONS IN THE DIGITAL AGE - Hety Devita; Muhamad Eko Wahyu Umaryadi; Musilatin Nikmah (CV. Adiba Aisha Amira, 2026)
This article analyses the evolution of financial management concepts through the perspective of agency theory and corporate value. The method used is a literature review. The results of the study found that agency theory has evolved from the classic principal-agent conflict to digital agency theory, which utilises AI monitoring, blockchain transparency, and real-time analytics to reduce agency costs while increasing firm value through Tobin's Q and market-to-book ratio. Digital transformation (DT) has proven to be a key enabler of corporate value through operational efficiency (RPA, predictive maintenance), governance transparency (smart contracts), and the creation of intangible assets (data platforms, ESG disclosure), despite showing a partial negative profitability effect on capital-intensive industries such as Indonesian mining (BUMI, ADRO). Strategic implications include hybrid governance models, capital structure optimisation based on intangible assets, and alignment of DT-company dynamics to achieve sustainable competitive advantage. Further research is recommended on empirical testing of digital agency theory in ASEAN emerging markets, moderated by digital maturity and institutional ownership.